2021
DOI: 10.1097/md.0000000000026478
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of antiepileptic drugs dose in pediatric children with epilepsy in Saudi Arabia

Abstract: This study aims to evaluate the effect of dose titration for different oral antiepileptic medications among children with epilepsy in Riyadh, Saudi Arabia. A single-center prospective pilot, cohort study was undertaken at a tertiary hospital in Riyadh, Saudi Arabia. All medical records of pediatric patients below the age of 14 years of age who has been newly diagnosed with epilepsy by attending a medical specialist or on a new epileptic treatment plans were enrolled in the study. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Alotaibi, Badriyah et al [27] also reported that in comparison to patients who followed the BNF guideline, the group who followed the standard practice was shown to have a higher rate of reported adverse effects. According to this study's findings, titrating antiepileptic medications are harmful to children.…”
Section: Resultsmentioning
confidence: 99%
“…Alotaibi, Badriyah et al [27] also reported that in comparison to patients who followed the BNF guideline, the group who followed the standard practice was shown to have a higher rate of reported adverse effects. According to this study's findings, titrating antiepileptic medications are harmful to children.…”
Section: Resultsmentioning
confidence: 99%